ENHANCING LEADERSHIP QUALITIES IN FEMALE STUDENTS: A MODERN PEDAGOGICAL AND PSYCHOLOGICAL APPROACH TO UNIVERSITY EDUCATION - Nilufar Bakhtiyarovna, Djabbarova (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to examine the pivotal role of university education in cultivating leadership qualities among female students by leveraging modern pedagogical and psychological strategies. The objective is to explore how personalized, humanistic-based educational methods contribute to developing essential leadership traits. Methods: The methods involve emphasizing open communication, fostering creative engagement, and promoting personal development tailored to individual needs. These approaches create a supportive and empowering environment that encourages students to actively realize their potential. Results: The results demonstrate that personalized educational practices not only enhance academic and social skills but also significantly strengthen leadership capacities, preparing female students for effective societal roles. Novelty: The novelty of this research lies in its integration of humanistic educational values with innovative teaching strategies to address the unique needs of female students, offering a practical framework for leadership development in higher education.